Oils and fats analysis - recent advances and future prospects - Che Man, Yaakob (2004)
Rapid and continued developments in electronics, optics, computing, instrumentation, spectroscopy and other branches of science and technology have led to considerable improvements in various analysis techniques. Due to this revolution in techniques, we are now able to solve problems, which were thought to be extremely difficult to do so a few years ago. These new techniques enable us to better characterize, monitor and authenticate oils and fats and improve our understanding of these important food constituents. Analytical techniques have now moved form the confines of the chemistry laboratory to from an indispensable part of the analytical armory of many researchers involved in the fields of oils and fats. Recent years have also seen a dramatic improvement in the ease with which analytical instruments can be used, and the quality and quantity of the analytical data that they can produce. Non-destructive techniques such as differential scanning calorimetry (DSC), Fourier transform infrared (FTIR), near-infrared (NIR) spectroscopy and electronic nose (EN) were developed and applied to analyse various quality characteristics of oils and fats products. The new techniques offer alternative to the use of time-and-work-consuming conventional standard methods and minimize the use of toxic chemicals that are hazardous not only to the analyst but also to the environment. These techniques are rapid, accurate, reliable and safe and potentially suitable for routine analyses in quality control laboratories. These analyses are important tools for analytical chemists, food professionals and regulatory authorities in ensuring compliance and enforcement becoming more educated, well informed and mire demanding on their rights to purchase quality food products, more research and analytical developments for food authenticity, especially for halal food, are needed. This lecture highlights recent advances on various analytical techniques and their potential applications for quality assessment and authentication of oils and fats.